Prevalence and Global Health Implications of Social Media in Direct-to-Consumer Drug Advertising - Liang, Bryan A; Mackey, Timothy K (JMIR Publications, 2011)
BackgroundDirect-to-consumer advertising (DTCA), linked to inappropriate medication use and higher health care expenditures, is the fastest growing form of pharmaceutical marketing. DTCA is legal only in the United States and New Zealand. However, the advent of online interactive social media "Web 2.0" technologies-that is, eDTCA 2.0-may circumvent DTCA legal proscriptions. ObjectiveThe purpose of this study was to assess the prevalence of DTCA of leading pharmaceutical company presence and drug product marketing in online interactive social media technologies (eDTCA 2.0). MethodsWe conducted a descriptive study of the prevalence of eDTCA 2.0 marketing in the top 10 global pharmaceutical corporations and 10 highest grossing drugs of 2009. ResultsAll pharmaceutical companies reviewed (10/10, 100%) have a presence in eDTCA 2.0 on Facebook, Twitter/Friendster, sponsored blogs, and really simple syndication (RSS) feeds. In addition, 80% (8/10) have dedicated YouTube channels, and 80% (8/10) developed health care communication-related mobile applications. For reviewed drugs, 90% (9/10) have dedicated websites, 70% (7/10) have dedicated Facebook pages, 90% (9/10) have health communications-related Twitter and Friendster traffic, and 80% (8/10) have DTCA television advertisements on YouTube. We also found 90% (9/10) of these drugs had a non-corporate eDTCA 2.0 marketing presence by illegal online drug sellers. ConclusionPharmaceutical companies use eDTCA 2.0 to market themselves and their top-selling drugs. eDTCA 2.0 is also used by illicit online drug sellers. Regulators worldwide must take into account the current eDTCA 2.0 presence when attempting to reach policy and safety goals.